2010
DOI: 10.1371/journal.pone.0010980
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the Proteome of Normal Human Cerebrospinal Fluid

Abstract: BackgroundKnowledge of the entire protein content, the proteome, of normal human cerebrospinal fluid (CSF) would enable insights into neurologic and psychiatric disorders. Until now technologic hurdles and access to true normal samples hindered attaining this goal.Methods and Principal FindingsWe applied immunoaffinity separation and high sensitivity and resolution liquid chromatography-mass spectrometry to examine CSF from healthy normal individuals. 2630 proteins in CSF from normal subjects were identified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
225
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 190 publications
(240 citation statements)
references
References 33 publications
15
225
0
Order By: Relevance
“…Additionally, ethical considerations limit the collection of CSF from healthy patients and, as a result, studies focusing on characterization of CSF from healthy individuals are limited [150,151]. One way to circumvent this issue is through investigation of urine-based biomarkers.…”
Section: Biomarkers In Urinementioning
confidence: 99%
“…Additionally, ethical considerations limit the collection of CSF from healthy patients and, as a result, studies focusing on characterization of CSF from healthy individuals are limited [150,151]. One way to circumvent this issue is through investigation of urine-based biomarkers.…”
Section: Biomarkers In Urinementioning
confidence: 99%
“…A further 11 proteins from the list were found in a study aimed at establishing the proteome of normal human CSF. [16] This leaves 41 proteins (Supplementary Table S3, see Supporting Information) that, to the best of our knowledge, have not previously been detected in CSF, suggesting they are of low abundance and usually below the limit of detection in proteomic studies. The detection of peptides from these proteins again highlights the benefit of a suitable TMTcalibrator ™ trigger.…”
Section: Tmtcalibratormentioning
confidence: 99%
“…Potential sources of these protein elevations include rupture of the ependymal surface (from IVH), release from ventriculomegaly induced parenchymal stretch, cleavage of native protein, sequelae from hemorrhage or inflammation, or from the IVH itself. Although the clinical design of the current study presents limitations in our ability to speculate on the source of the proteins, we can utilize the work of Schutzer et al (11) and others to provide insight into this issue. Schutzer et al used IgY-14 LC-MS to compare proteins in the CSF of adult humans to those observed in plasma from a cohort of trauma patients and found a large percentage (56%) of proteins that appeared to be present only in CSF.…”
Section: Discussionmentioning
confidence: 99%